Mongolia Economic Retrospective 2008-2010 - World Bank (World Bank, 2012)
Mongolia was one of the East Asian economies hardest hit by the global downturn, as copper prices collapsed and external demand fell. With the recovery in economic activity currently well underway, but the policy challenges highlighted by the crisis yet to be fully addressed, this economic retrospective examines the key economic, financial, and policy developments from mid 2008 to April 2010. Collapsing mineral prices and a steep drop in external demand due to the global downturn of 2008 and 2009 were the external shocks which were transmitted to Mongolia's economy. This shock exposed underlying weaknesses in the economic structure and policy environment. More generally, now is the time to put in place a strong policy framework to manage the upcoming mining boom and avoid the mistakes of the past. The looming mining boom brings the risks of "Dutch disease" effects and a return to the profligate populism of the past. Measures to address these risks include the recently adopted fiscal stability law that will help the country move away from the fiscal boom and bust cycles of the past; improvements to the budget process and the planning and management of public investments in order to more efficiently absorb the large projected increases in revenues; and appropriate policy frameworks to support future infrastructure investment. Implementing a targeted poverty benefit should also ensure the poor are protected from mining boom and busts in a fiscally sustainable manner. Finally, continued reforms in the mining sector will enhance incentives for new exploration and environmentally and socially sustainable development.